The Context and Trend to Develop the Pre-Working Training Course for Promoting the Competency, Capacity and Ability in the Business Service Field in ASEAN Countries - Pholpuntin, Sirote; Bhulapatha, Prakit; Chanjaroen, Phitak; Shusatayasakul, Nerru; Chuenpraphanusorn, Teeradet; Snguanyat, Ongrn (Richtmann Publishing, 2019)
The investigation of this research had 3 main objectives: 1) to study, survey and analyze the context, trend, competency, capacity and ability in the business service field in ASEAN countries, 2) to develop the competency standard in the business service, and 3) to discuss the competency standard that relevance to the need of the ASEAN workers in the business service field. The instrument of this research was a questionnaire, and was divided into three-parts, totally 29 items, the reliability by Cornbrashâ€™s Alpha = 0.98. Then collected for 258 participants by the accidental sampling methods. The data was analyzed by Mean, Standard-Deviation, t-test and one-way ANOVA for hypothesis testing. The result (s) was reviewed by step to step such; Step 1) a) the demographics of the sampling group, most of the sampling were female, totally 162 persons, representing 62.79%. 51 people aged up 40, representing 25.37%. 112 people had a bachelor degree, representing 43.41%. 100 people from the Philippines, representing 38.76%. b) The competency that the business service officer should have or should be. The overall opinion on the competency that it should have or should be at highest needs (mean = 4.22, s.d. = 0.56), when considering by the aspects, it was found that; the opinion on the organizational and perspective on the highest need came first, followed by the personal and service skills. And the opinion on the communicative skills at highly need came last, respectively. C) The hypothesis testing was found that the result of comparing the competency that the business service office should have or should be by gender, such; the sampling who difference gender had a similar overall opinion on the competency that the business service office should have or should be. And when considering by the aspect it was found that; the sampling who difference gender had a similar opinion on the competency in all aspects. Step 2) in each competency includes a definition and the observable behaviors (skills) that may indicate the existence of a competency in a business service person. These crucial competencies are divided into two types of competencies both the core competency and the functional competency and then are separated into the several 'clusters.', especially 19 (similar competencies related to a common skill set). Step 3) to discuss the competency standard. From the workshop and the focus group of the expertise, it can be concluded that the thinking skills are also the best way to develop the human in all careers because of many jobs need the human who also has awareness in their duties, responsibilities and concern in their job. Moreover, both of four subcategories of the thinking skills such, 1) the analytical and critical thinking skills, 2) the forward thinking skills, 3) conceptual thinking skills and, 4) the strategic thinking skills are suitable for this field of work. From the group discussion can be concluded that the â€œEstablish the goalsâ€ should be the first priority of management in any fields of work as well as the business service, because the organization can set the goal(s) and develops a plan(s) to help fulfill the service businessâ€™ mission. The comparison and discussion made clear that â€œthe core competency standardâ€ are adopted in several areas of the business service job both from the survey research and focus group discussion. In spite of the core competency is looking like the main organ of the human body, but it cannot avoid that the functional competency is also the supporting organ of the body too. Additionally, the group discussion is also analyzed that the â€œCooperative Relationships and Teams Workingâ€ can be seen from the performance of the officer in the business service. Every job can be done by the good relationship of the colleagues and partner, so the business service jobs of the ASEAN should be established the organization in cooperation.